Plasticity in aggression and the correlated changes in the cost of reproduction in male Drosophila melanogaster. (April 2016) - Nandy, B.; Dasgupta, P.; Halder, S.; Verma, T.
Abstract : In many animals, the nontrivial cost of ejaculate production has led males to evolve prudent reproductive strategies in the form of precopulatory mating bias and/or cryptic ejaculate allocation. Behaviours determining male reproductive success, such as courtship and aggression, also impose substantial costs potentially selecting for plasticity in these traits. Here, using laboratory-adapted populations of Drosophila melanogaster, we investigated whether males show plasticity in these behaviours in response to the changes in their perception of future risk of competition (generated by varying the number of rivals). We show that males exhibited nonlinear plasticity in their aggressive behaviour. Males subjected to intermediate risk were found to show the maximum level of aggression compared to those subjected to low and high risk. Such plasticity in aggression did not lead to any variation in mating success but significantly increased the cost of reproduction. We also found a similar trend in courtship behaviour. While our results on copulation duration confirmed the previously reported plasticity, we did not find any effect of the treatment on mating latency. To the best of our knowledge this is the first empirical evidence showing plasticity in aggression in response to perceived risk of future competition and its relation to the cost of reproduction. Highlights: We studied laboratory-adapted populations of Drosophila melanogaster fruit flies. Males can perceive future risk of competition by the number of rivals around. Males respond by showing plasticity in copulation duration and aggressiveness. Mating latency and mating success were not affected. Plasticity in aggression alters males' survival under starvation and desiccation.